Selective predation on common voles by Tawny Owls and Long-eared Owls in winter and spring - Balčiauskas, Linas; Balčiauskienė, Laima (TURKISH JOURNAL OF ZOOLOGY, 2014)
We studied size preferences of Tawny (Strix aluco) and Long-eared (Asio otus) Owls preying on common voles (Microtus arvalis) in the winter and spring seasons in Central Lithuania. Regression equations were used for body mass estimations. We found that both A. otus and S. aluco preferred larger M. arvalis than the average available in the population (the average body mass of predated individuals was 21.45 ± 0.12 g compared to 16.42 ± 0.16 g of snap-trapped individuals). Irrespective of the owl species, most of the predated Microtus voles were adults. In S. aluco prey, the winter proportion of young voles was significantly higher than in the prey of A. otus, 33.3% versus 5.2%. By contrast, the proportion of subadult and adult voles with a body mass in the range between 19 and 23 g was significantly higher in the prey of A. otus. Our results may indicate that the selection of the differently sized prey allows the 2 species of owls to coexist sympatrically.